Early Intervention is Important to Prevent Sensitization to New Allergens - Terada, Tetsuya (Med Sci (Basel), 2018)
We review current management for allergic rhinitis and possible new treatments for this condition. Management of allergic rhinitis includes promotion of protective factors, avoidance of allergens, and possibly immunotherapy. In recent years, the incidence of allergic rhinitis has increased in many countries. Early intervention at different stages is an important part of management. Allergic disease in infants has been described as the allergic march, commencing with atopic dermatitis accompanied by infantile asthma and progressing to perennial allergic rhinitis induced by house dust mite allergy. In order to prevent polysensitization, allergen-specific immunotherapy should probably be initiated at an earlier age, especially in children with rhinitis who show monosensitization to house dust mite antigens.